A Chronological Literature Review of Different Augmented Reality Approaches in Education - Pathania, Manisha; Mantri, Archana; Kaur, Deepti Prit; Singh, Chander Partap; Sharma, Bhanu (Technology, knowledge and learning, 2023)
Over the past numerous years, the training structure is applying outdated strategies that keep schools from moving to competency-based models. Since most of the parts are instructor-oriented, the students are the detached party in the classroom which prompts less communication between students and the instructor. Augmented Reality (AR) is an interactive technology that reshapes the classroom learning environments by providing a means to interact with the course and the instructor dynamically. The learning process can be made more effective, efficient, and expressive when AR is implemented in education. Recently, many research efforts have been made for merging AR with teaching because of its ability to provide an immersive and interactive environment. Furthermore, this work discusses the benefits of AR compared to customary technical platforms (such as e-learning, MOOC courses, and virtual reality) and traditional schooling approaches (chalk and talk and old-style books). Additionally, this work presents the studies that have been carried out on AR, outlines and provides a chronological review of the different approaches of AR being executed in training and education. The paper also highlights the present state of the art research, how the technology trend has changed over the years, and which subjects and their corresponding domain have been explored.